Pengaruh Konsumsi Masyarakat Indonesia terhadap Ketahanan Pangan Nasional - A.W, Vilentine Tessalonica; Fitriyani, Arum Eka; Febrianti, Mita; Lesmana, Muhammad Erza; Lukman, Raif Maulana; Budiasih, Budiasih (Politeknik Statistika STIS, 2023)
Food is a basic need for humans to be able to live and improve their lives. The Global Food Security Index (GFSI) and the Food Security Index (IKP) are each a measure of how good food security is in the world and Indonesia. In 2022 Indonesia's GFSI score is ranked 69th in the world and sixth in ASEAN countries. Indonesia's GFSI has also decreased from 2018 to 2021. The purpose of this study was to analyze the effect of consumption on a decrease in the level of food security as reflected in Indonesia's GFSI scores for the 2018-2021 period based on 2 GFSI aspects, namely Affordability and Availability. The data used is panel data from 34 provinces in Indonesia from 2018 to 2021 which were analyzed using the panel data regression method. The Random Effect Model (REM) was chosen as the best model in this study with the results showing that Rice Productivity, Total Rice Consumption, and Protein Consumption have a positive and significant effect on the Level of Food Security.